Myriocin enhances the antifungal activity of fluconazole by blocking the membrane localization of the efflux pump Cdr1 - Wang, Hongkang; Ji, Zhe; Feng, Yanru; Yan, Tianhua; Cao, Yongbing; Lu, Hui; Jiang, Yuanying (Frontiers in Pharmacology, 2022)
Extrusion of azoles from the cell, mediated by an efflux pump Cdr1, is one of the most frequently used strategies for developing azole resistance in pathogenic fungi. The efflux pump Cdr1 is predominantly localized in lipid rafts within the plasma membrane, and its localization is sensitive to changes in the composition of lipid rafts. Our previous study found that the calcineurin signal pathway is important in transferring sphingolipids from the inner to the outer membrane. However, in the present study, we found that this signal pathway has no function in the activity of Cdr1. We further investigated multiple factors that enhance the antifungal activity of fluconazole (FLC). We found that inhibiting sphingolipid biosynthesis by myriocin remarkably increased the antifungal activity of FLC with a broad antifungal spectrum and held therapeutic potential. We further found that myriocin potently enhances the antifungal activity of FLC against C. albicans by blocking membrane localization of the Cdr1 rather than repressing the expression of Cdr1. In addition, we found that myriocin enhanced the antifungal activity of FLC and held therapeutic potential evaluated by a mouse candidiasis model. Our study demonstrated that blocking the membrane location and inactivating Cdr1 by inhibiting sphingolipids biogenesis is beneficial for enhancing the antifungal activity of azoles against azole-resistant C. albicans due to Cdr1 activation.